Reaction Speed and Coordination Improves The Punch of Gyaku Zuki Chudan (Department of Physical Education, Sport, Health and Recreation, 2020)
This study aims to determine the effect of reaction speed, eye-hand coordination towards the gyaku zuki chudan on Bandung Karate Club Athlete in Bekasi City. The research method is a descriptive associative, and the analysis technique is path analysis. The sampling technique used is a total sampling with a sample amount of 16 people. The instruments used are a test of gyaku zuki chudan, reaction speed measurement using Catch the ruler test, eye-hand coordination measurement using throw-catch the ball, The amount of value obtained by gyaku zuki chudan technique is to do a straight punch parallel to the chest or angle of the 90Â° with as soon as possible for 10 seconds. Samples tested 2 times, performed in a closed room, the results obtained in the execution of the test is hitting in the size of the number of punch. The conclusions are: (1) reaction speed directly affects on the gyaku zuki chudan, and (2) eye-hand coordination directly affects on the gyaku zuki chudan.